Metal-THINGS: The Milky Way twin candidate NGC 3521 - Pilyugin, L. S. (2025)
The 3D spectrophotometry measurements of the galaxy NGC 3521, a structural Milky Way analogue (sMWA), were carried out within the Metal-THINGS project. We found that the oxygen abundance in the inner part of NGC 3521 is at a nearly constant level and the O/H gradient is negative at larger radii. The change in the nitrogen abundance with radius is similar to that for oxygen with the break in the N/H distribution at a smaller radius than the O/H distribution break, but the difference between the break radii is within the uncertainties of these values. The radial distributions of the oxygen abundance, the gas mass fraction, and the effective oxygen yield in NGC 3521 are compared to that of the Milky Way (MW), with the aim of examining the similarity (or disagreement) in their chemical evolutions. The oxygen abundances of two H II regions closest to the centre of the MW (at a radii of 4–5 kpc) are close to the binned oxygen abundances in NGC 3521 at the same galactocentric distances; an accurate value of the central oxygen abundance in the MW cannot be established because of the lack of the measurements near the centre. The oxygen abundances in the outer part of the MW are lower than those in the outer part of NGC 3521. The gas mass fraction in the outer part of the MW is higher than in NGC 3521. The obtained values of the effective oxygen yield, Yeff, in NGC 3521 are close to the empirical estimation of the oxygen yield, YO. This suggests that mass exchange with the surroundings plays little to no role in the current chemical evolution of NGC 3521. The values of the Yeff in the MW were determined using two variants of the radial distribution of the gas mass surface density. The values of the Yeff in the MW obtained with the first distribution are also close to YO, as in NGC 3521. The Yeff in the MW obtained with the second distribution are below YO at radii between ∼6 and ∼10.4 kpc. This suggests that the mass exchange with the surroundings can play a significant role in the chemical evolution of this part of the MW, in contrast to that in NGC 3521. To draw a solid conclusion about the role of mass exchange with the surroundings in the chemical evolution of the MW it is essential to determine which of these distributions provides a more adequate description of the gas distribution in the MW.